Modulation of the absorption properties of a novel iron trisbipyridyl complex by introducing peripheral ruthenium ammines - Mecchia Ortiz, Juan Hugo (2017)
The novel trisbipyridyl iron complex of formula [Fe(Mebpy-CN)3](PF6)2 (1) (with Mebpy-CN = 4-methyl-2,2′-bipyridine-4′-carbonitrile) and three novel heteropolynuclear complexes of formulae: [(Mebpy-CN)2Fe(Mebpy-CN)Ru(NH3)5](PF6)4 (2), [(Mebpy-CN)Fe{(Mebpy-CN)Ru(NH3)5}2](PF6)6 (3) and [Fe{(Mebpy-CN)Ru(NH3)5}3](PF6)8 (4), were synthesized and characterized by spectroscopic and electrochemical techniques. When introducing peripheral ruthenium ammines to complex (1) using Mebpy-CN as a bridging ligand in complexes (2) to (4), the molar absorptivities increase in the visible region with increasing nuclearity of the complex. When oxidizing the Ru centers in the heteropolynuclear species, the corresponding three mixed-valent species are obtained, displaying IVCT (intervalence charge transfer) bands at λmax = 850 nm, with molar absorptivities that are also enhanced by increasing the number of pentaammineruthenium moieties. The modulation of the absorption properties of transition metal complexes in the visible and NIR regions is a relevant issue for improving the performance of Dye-Sensitized Solar Cells, since their efficiency can be enlarged with increasing absorption in these regions.